Implementasi GForm Dalam Mendukung Kegiatan Lomba Pada Organisasi Fatayat Ciledug - Syahriani; Frisma Handayanna; Maryanah Safitri; Tri Santoso (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The use of information and communication technology has had an impact on the use of information and communication technology in various fields related to administration. The use of technology is increasingly common among today's society, including the use of computers, tablets and smartphones. Technological advances have also made it easier to use information and communication technology in administrative work, especially with internet access becoming more easily accessible. Like Fatayat NU, the Islamic Women's Organization also has religious, social and familial aspects. This organization still has many problems that are not yet understood in implementing their activities using information technology, especially in terms of management. Fatayat NU Ciledug is facing several obstacles in managing the creation of attendance forms or participants taking part in competitions for its activities, including a lack of understanding of Google Forms and forms that are not filled out completely. One step to solve this problem is to carry out community service to help provide an understanding of (1) the use of Google Forms and (2) the creation of Google Forms. The service method used consists of four steps, namely: (1) Planning step; (2) preparatory steps; (3) implementation steps and (4) evaluation steps. The result of this community service activity is an increase in the ability of female Fatayat NU Ciledug members in creating forms using Google Forms, as well as developing their knowledge and skills. Apart from that, this activity was published in the editorial media of a national journal.